High prevalence of vector-borne pathogens in the blood of clinically healthy dogs in Hong Kong - Thamali Manathunga; Mariaelisa Carbonara; Omid Nekouei; Jairo Alfonso Mendoza-Roldan; Wing Yan Jacqueline Tam; Frederic Beugnet; Domenico Otranto; Vanessa R. Barrs (Parasites & Vectors)
Abstract Background Leishmaniosis and other canine vector-borne diseases (CVBDs) pose a major risk for veterinary and public health globally, especially where humans and dogs live in close proximity. Although mosquito and tick vectors are abundant in Hong Kong, surveillance for CVBDs has been limited. Methods A serological and molecular survey of 158 healthy owned (n = 64) and free-roaming unowned (n = 94) dogs with outdoor access in Hong Kong was performed to determine CVBD prevalence. Point-of-care (POC) immunoassays were used to detect (i) antibodies to Leishmania spp., Ehrlichia spp., and Anaplasma spp., and (ii) Dirofilaria immitis and Angiostrongylus vasorum antigens, in canine sera. Conventional polymerase chain reaction (PCR) was also carried out to detect the molecular prevalence of all five pathogens as well as Hepatazoon canis, Babesia gibsoni, and Trypanosoma evansi. In addition, for Leishmania spp. detection, an immunofluorescence antibody test (IFAT) was performed on all serum samples, followed by real-time PCR of seropositive samples to detect Leishmania spp. DNA. The agreement between tests was assessed by Cohen’s kappa statistic, and logistic regression analysis was applied to identify potential risk factors. Results Overall, 45.6% of dogs tested positive on molecular and/or serological tests for at least one pathogen, with the highest prevalence recorded for Dirofilaria spp. (20.9%), followed by B. gibsoni (15.2%), Leishmania spp. (11.4%), Anaplasma spp. (7.6%), H. canis (4.4%), Ehrlichia spp. (3.8%), and A. vasorum (0.6%). No T. evansi DNA was detected. Co-infections or co-pathogen exposure occurred in 16.5% of samples. Of the 33 Dirofilaria spp.-positive dogs, two were identified by sequencing as Dirofilaria asiatica, and the remaining 31 were D. immitis. No significant risk factors for infection or exposure were identified. Conclusions This is the first epidemiological survey of Leishmania spp. infection in dogs from Hong Kong, highlighting the need for surveillance of competent vectors and further investigation of disease status in dog populations to confirm whether this pathogen is endemic. Given the high prevalence of CVBD, especially of D. immitis, preventive and control measures are advocated in order to mitigate risks to canine health and zoonotic infection. Graphical abstract